Arterial hypertension and stroke: cardiac and neurological aspects of secondary prevention - L.A. Geraskina (Неврология, нейропсихиатрия, психосоматика, 2014)
This article considers the pathogenetic mechanisms of stroke in arterial hypertension (AH) with special emphasis on comorbid neurological and cardiac disorders. It presents the cardiac and neurological aspects of the current strategy of medical therapy within the secondary prevention of poststroke cardiovascular events. The secondary prevention of cardiovascular events in patients who have sustained ischemic stroke in the presence of AH involves the use of not only antihypertensive drugs, but also adequate antiplatelet therapy and statins. The most important part is assigned to the prevention and treatment of cognitive impairments, which also promotes increased patient treatment adherence and improved poststroke prognosis, including longer survival and better quality of life.